Creating space for learning through 'Mm hm' in a L2 classroom: Implications for L2 classroom interactional competence. Issue 1 (2nd January 2020) - Girgin, Ufuk; Brandt, Adam
ABSTRACT: Studies on Second Language (L2) classroom interaction have placed a great deal of emphasis on the value of teacher third-turn feedback practices. However, the roles that seemingly minor aspects of interaction like minimal response tokens (e.g. 'Mm', 'Mm hm', 'Uh huh', 'Okay', 'Yeah') play as a feature of these practices have not been investigated in great detail. Studies which have sought to examine what such tokens do in language teaching and learning processes have mostly adopted a discourse analytic perspective, thereby treating them more or less as a homogeneous group (namely, 'backchannel signals'). However, through ethnomethodological research, each token has been found to be doing distinctive work. This study adopts a multimodal conversation analytic perspective to investigate the uses of 'Mm hm' by an English as a Foreign Language teacher in a teacher education context. Analysis demonstrates how the teacher uses the token as a 'continuer' to withhold a third-turn evaluation, thereby keeping the channel open for further participation and hence creating space for learning. As such, the study furthers our understanding of L2 teachers' third-turn feedback practices and has direct implications for L2 teacher classroom interactional competence.